Administration of intramuscular medication in the ventrogluteal region: evaluation after videoconference training - Simone de Godoy; Maria Suely Nogueira; Miyeko Hayashida; Isabel Amélia Costa Mendes (Rev Rene)
The purpose of this study was to encourage the use of the ventrogluteal region. One developed training on the contents of the administration of intra-muscular medication in the mentioned region directed to nursing auxiliaries of a University Hospital located in the countryside of the state of São Paulo. The videoconference technique was used to link the laboratory at a state Nursing College with the Hospital in order to broadcast classes. The training was developed in a simulated present situation. The 30 nursing auxiliaries were evaluated regarding intellectual and motor skill acquisitions and had a good performance in the procedure of the simulated situation.